2015
DOI: 10.15351/2373-8456.1024
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Reef Attributes and The Relationship With Natural Reefs: Evidence From The Florida Keys

Abstract: Natural or coral reefs represent extremely valuable ecosystems supporting an estimated 25 percent of all marine life, yet recent reports suggest that 75 percent of the world's natural reefs are under threat from both natural and human stressors. In areas such as the Florida Keys that boasts an expansive mix of natural and artificial reefs, recreational diving on the system provides an important economic contribution to the local community but also potentially contributes to the stress of the existing natural r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In conclusion, long-term studies emerge once again as crucial components in shaping sustainable marine conservation strategies. The establishment of well-designed artificial reefs (ARs) serves as an effective means to divert human pressure, particularly guided divers, away from natural coral reefs, thereby aiding in the preservation of these vulnerable ecosystems [25,[28][29][30][31][32][33][34][35][36][37][38][39]. The emphasis on meticulous design becomes imperative, ensuring that ARs remain not only visually appealing but also biologically vibrant over extended periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, long-term studies emerge once again as crucial components in shaping sustainable marine conservation strategies. The establishment of well-designed artificial reefs (ARs) serves as an effective means to divert human pressure, particularly guided divers, away from natural coral reefs, thereby aiding in the preservation of these vulnerable ecosystems [25,[28][29][30][31][32][33][34][35][36][37][38][39]. The emphasis on meticulous design becomes imperative, ensuring that ARs remain not only visually appealing but also biologically vibrant over extended periods.…”
Section: Discussionmentioning
confidence: 99%
“…The instructor briefs and prepares the visitor, closely monitors and guides him/her, and, in essence, leads the visitor on an underwater tour during the dive. In Israel, such introductory dives typically last between 30 and 40 min, and they are restricted in depth, not exceeding 6 m [33]. Although the guests or tourists are controlled by the instructor, and they receive briefings on how to avoid harming the underwater wildlife, these divers sometimes exhibit unsteady behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Kasim et al (2013) found that the revenues of commercial fishers in India were over twice as high on artificial reefs compared to non-artificial reef areas, whilst Johns et al (2001) observed that recreational divers in South-East Florida were willing to pay over twice as much to protect natural reefs (USD 229.3 million/year) than to protect a shipwreck (USD 85.1 million/year). However, Huth et al (2015) found that dive tourists in Florida had a higher willingness to pay for a dive trip to a shipwreck (USD 368) than to natural reefs (USD 300), whilst Islam et al (2014) found that the monthly fishing income from artisanal fishers on an artificial reef in Malaysia was lower than on adjacent natural reefs.…”
Section: Comparison Of Values For Mms and Natural Marine Habitatmentioning
confidence: 99%
“…Tables 2 and 3 provide a breakdown of some key user characteristics from both treatment samples from our 470 responses. As is typical of samples from other diver-related studies, our sample diving population is a well-educated, high income-earning cohort (see Morgan et al 2009 andHuth et al 2015). For example, respondents from both samples earn an average annual salary of over $120,000 with approximately 75 percent earning at least a bachelor's degree.…”
Section: Cultural Worldview and Voting Behaviormentioning
confidence: 99%